Next generation sequencing-aided screening, isolation, molecular identification, and antimicrobial potential for bacterial endophytes from the medicinal plant, Elephantorrhiza elephantina - Tlou, Matsobane; Ndou, Benedict; Mabona, Nokufa; Khwathisi, Adivhaho; Ateba, Collins; Madala, Ntakadzeni; Serepa-Dlamini, Mahloro Hope (Frontiers in Microbiology, 2024)
Elephantorrhiza elephantina, a wild plant in southern Africa, is utilized in traditional medicine for various ailments, leading to its endangerment and listing on the Red List of South African Plants. To date, there have been no reports on bacterial endophytes from this plant, their classes of secondary metabolites, and potential medicinal properties. This study presents (i) taxonomic characterization of bacterial endophytes in leaf and root tissues using 16S rRNA, (ii) bacterial isolation, morphological, and phylogenetic characterization, (iii) bacterial growth, metabolite extraction, and LC-MS-based metabolite fingerprinting, and (iv) antimicrobial testing of bacterial crude extracts. Next-generation sequencing yielded 693 and 2459 DNA read counts for the rhizomes and leaves, respectively, detecting phyla including Proteobacteria,